Ανάπτυξη Έξυπνων Συμβολαίων στο Blockchain και εφαρμογή στο IoT - Παπαδόδημας, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής και Συστημάτων Πληροφορικής, 2018)
The revolution of the Internet changed the way most people understand the world and now is part of our everyday lives. The technologies on which it is based on are rapidly evolving while new technologies are invented. A feature that remained unchanged for many years is the client-server architecture, which is being used on most applications and services available on the Internet. This is about to change, thanks to newly introduced technologies, among which are the blockchain and the Internet of Things (IoT) that may decentralize the Internet. Blockchain technology was originally devised in order to serve the cryptocurrency Bitcoin, but it evolved and now its scope is very broad. The blockchain is a dig-italized distributed ledger of transactions. Besides the cryptocurrency, blockchain can be used for the creation and operation of decentralized applications (DApps), scilicet applications that are based on a peer to peer network rather than an organization’s server for their operation. An example of this feature of the blockchain, is Ethereum, a Turing complete distributed computing architecture, a platform for developing and deploying decentralized applications through smart contracts. Technologies of the Ethereum tech-nology stack are being used in this thesis. The purpose of this diploma thesis is the engagement with the decentralization technologies of the IoT and the blockchain as well as the development of a decentralized application (DApp) that will combine the two previous fields. This application operates through smart contracts that are executed on the Ethereum blockchain and combines blockchain technology with IoT. More specifically, “Crypto Weather”, as is the name of the application, is a platform for sharing (buying and selling) measurements of IoT weather sensors that operates on the Ethereum blockchain. This diploma thesis, includes a presentation on the theoretical matters of the de-centralized web and its component technologies. A presentation of the development process of the decentralized application “Crypto Weather” is also included, as well as a presentation of the application itself.